Analisa Perilaku Pengambilan Risiko Pembiayaan Perbankan Syariah Di Indonesia : Analysis of Risk Taking Behavior of Islamic Banking Financing in Indonesia - Regina Putri Listyadewi (Universitas Darussalam Gontor, 2023)
The basic principles attached to Islamic banks direct Islamic banks to minimize their exposure to excessive financing. However, various previous studies have shown the tendency for financing by Islamic banks to take excessive risks. On the other hand, this type of sharia financing contract tends to be protective in a downturn in the economy. The purpose of this study is to analyze the risk-taking behaviour of Islamic banks in financing and their response to the economy. This study uses a qualitative approach with technical analysis of literature studies. The result is that financing by Islamic banks at a certain Non-Performing Financing (NPF) threshold can lead them to take bold risks. The comparative advantage that exists in this type of Islamic bank financing is countercyclical so that it can withstand deterioration in a declining economy.Keywords: Excessive risk; Islamic bank financing; Risk-taking behaviour